The Influence of Plant Type, Substrate and Irrigation Regime on Living Wall Performance in a Semi-Arid Climate - Rosmina, Ahmad Bustami; Simon, Beecham; James, Hopeward (MDPI Switzerland, 2023)
Living walls are fast becoming a ubiquitous feature of modern living and are widely implemented in commercial buildings in both internal and external environments. However, there are several challenges associated with maintaining healthy plant growth on these water sensitive urban design systems. This experimental study of an instrumented prototype-scale living wall has found that there is a close relationship between the plants, substrates and adopted irrigation regimes. In this study, plant selection was found to be more critical than either substrate or irrigation regime selection. This research also found that both the location of the plants on the wall and irrigation volume significantly affected the plants’ ultimate total dry weight. In particular, plants were found to grow taller on the upper section of the living wall compared to the middle and lower sections. It is recommended that particular attention should be given to plant location and the amount of irrigation water supplied at different positions on the living wall.